Techtutor: AR-integrated learning application for computer and technology use - Loh, Chia Heung (2025)
In today’s digital era, the ability to operate basic computer technologies has become increasingly important. However, many beginners and older adults continue to face difficulties in learning digital tools such as email, word processors, and calculators, mainly due to the lack of accessible and interactive resources. This project addresses this issue by developing TechTutor, an Augmented Reality (AR)-integrated and Artificial Intelligence (AI)-assisted mobile learning application designed to provide a simple, intuitive, and engaging platform for digital literacy. TechTutor was developed using Unity 2022.3.57f1, AR Foundation (ARCore and Vuforia), and OpenAI integration, following the Agile Software Development methodology. The system consists of 3 main components: AR Learn, which enables users to identify computer components, interact with 3D models, and attempt AR-based quizzes; AR Guide, which provides step-by-step AR tutorials for tasks such as sending an email, using Microsoft Word, the Snipping Tool and a calculator; AI Tutor, which offers chatbotbased assistance with both text and image inputs, enhanced by EasyOCR for keyword detection and contextual guidance. Speech-to-Text (STT) and Text-to-Speech (TTS) technologies were integrated across the modules to enable hands-free navigation, interactive feedback, and accessibility for diverse user needs. The novelty of TechTutor lies in combining AR-driven experiential tutorials and AI-powered assistance with keyword highlighting, creating an adaptive learning environment tailored for users with minimal prior exposure to computers and technology. By delivering immersive, interactive, and personalized guidance, TechTutor aims to reduce the digital divide and promote inclusive technology use among underserved groups, particularly the beginners and older adults.